Journal of Midwifery and Women's Health Vol.57 No.4, July/Agust 2012 - Redaksi (Elsevier, 2012)
- Electronic Health Records and Perinatal Quality: A Call to Midwives - Trens in Midwife-Attended Births in the United States, 1989-2009 - Evaluating Body Mass Index-Specific Trimester Weight Gain Recommendations: Differences Between Black and White Women - ...